The prophecy of green Arabia and the possibility of miracle: a refutation of David Hume’s theory of no miracle - Ahmad H.Osman, Rahmah; Ahmed Siddiqui, Naseeb (Hamdard Foundation, 2021)
Despite the claim of scientific methodology to avoid revelation as a source of knowledge, the revelation inherently is science-friendly, and for some cases, the torchbearer unveils the mysteries of this universe. Hence, it can surely benefit the natural sciences particularly and humanity in general; and there are numerous apodictic connecting the revelation and the universe. However, western scholars, specifically David Hume denied altogether such relation that amplifies his argument to no miracle fantasy. This article attempts to analyse one of the prophecies of Prophet of Islam Muhammad (Øal Allah-u-‘alaihe wa sallam), regarding an ancient event that fixed the course of earth’s behaviour and hence further aggrandizes the deep democracy working beneath the verses and natural laws. This prophecy, according to ×adÊth claims to engage with the ecological changes occurred in the Arabian Peninsula in the ancient time and unveils that Arabian Peninsula will become green again with rivers flowing abundantly. It signifies that Arabia was green and will return to its previous state of greenery in the future. At first, this research narrates and explains the ×adÊth in detail followed by an exposition of David Hume’s no miracle theory based on testimonies. The arguments have been presented to support the idea of a green Arabia in the past and how it will regain its greenery by considering scientific facts so far. It became apparent that, while considering the ice and warm ages along with abundant natural resources, the ×adÊth is proven. It led to the complete denial of David Humes’s no miracle theory according to his definition of testimonies. Therefore, this paper established two important aims, at first, it breaks the conventional framework of Western scholarship that did toil attempts to alienate revelation as a source of knowledge. Second; for the first time it brings such a ×adÊth and contextualizes it with scientific facts, besides providing answers of the implications. Moreover, how the revelation describes the process of earth-in-making through ecological changes of millions of years. Hence, the Miracle is a part of natural law.